2012
DOI: 10.2147/opth.s33030
|View full text |Cite
|
Sign up to set email alerts
|

Results of nonendoscopic endonasal dacryocystorhinostomy

Abstract: BackgroundSurgical scarring on the face and disrupted anatomy in the medial canthal area following external dacryocystorhinostomy (DCR) can be avoided by an endonasal approach. This study examined the outcome of direct visualization endonasal DCR, performed by young surgeons and residents.MethodsA retrospective case series of 75 consecutive endonasal DCRs performed under direct visualization from July 2002 to July 2004 were reviewed. Surgery was performed by surgeons and residents who had received no special t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
(41 reference statements)
0
18
0
1
Order By: Relevance
“…[1] Varying results have been reported for endoscopic DCR; however, Onerci et al [21] indicated that the surgical success rate of endoscopic DCR in the hands of experienced surgeons was 94.4%, whereas inexperienced surgeons had a success rate of only 58 percent. [2] Many factors influence the success or failure of DCR. Regarding improved surgical success, the size and location of the osteotomy is important.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[1] Varying results have been reported for endoscopic DCR; however, Onerci et al [21] indicated that the surgical success rate of endoscopic DCR in the hands of experienced surgeons was 94.4%, whereas inexperienced surgeons had a success rate of only 58 percent. [2] Many factors influence the success or failure of DCR. Regarding improved surgical success, the size and location of the osteotomy is important.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Additionally, mitomycin C has been reported to delay wound healing or prevent scarring at the ostial opening. [2] Furthermore, the distal canalicular membranous obstruction is an anatomic factor that may lead to surgical failure if not identified and excised and in these cases, an external DCR procedure combined with membranectomy performed through the distal canalicular opening is recommended. [23] Laser-assisted DCR is an alternative to the standard external DCR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations